INTRAUTERINE PROTEOLYTIC ENZYME THERAPY FOR SUBCLINICAL ENDOMETRITIS IN DAIRY CATTLE - SINGH, J; HONPARKH, M; GHUMAN, S P S; KUMAR, A; DHINDSA, S; CHANDRA, M (The Indian Journal of Animal Reproduction, 2022)
Intrauterine (I/U) administration of proteolytic enzymes for treating subclinical endometritis was investigated in dairy cattle exhibiting subclinical endometritis that was diagnosed on the basis of apparently clear cervico-vaginal mucus and uterine cytobrush cytology (≥4% PMN cells). At spontaneous estrus, subclinical endometritic cattle were administered either single I/U infusion of Mastivexym ointment (trypsin 8 mg, chymotrypsin 8 mg, papain 4 mg, α-tocopherol acetate 120 mg and retinyl palmitate 58.83 mg; Group I, n=10) or single I/U infusion of crude formulation of aforesaid enzymes and vitamins in similar quantities dissolved in 10 ml distilled water (Group II, n=10). Ten subclinical endometritic cattle were kept as control (Group III). On day 12 after spontaneous estrus, all these animals were administered (i.m.) a PGF2α analogue (Cloprostenol 500 µg). This followed administration (i.m.) of GnRH analogue (Buserelin acetate, 20 µg) at the start of induced estrus. About 12-14 h after GnRH analogue, cattle were artificially inseminated twice at 12 h interval. At spontaneous and induced estrus, all these cattle were subjected to cytobrush technique for assessing PMN%, and microbial assay of cytobrush for bacterial load. Following enzyme therapy at spontaneous estrus, a reduction (p<0.05) in PMN% and bacterial load was observed at subsequent induced estrus in treated animals. Also, first service pregnancy rate were higher (p<0.05) in treated groups compared to control counterparts (50 vs. 20%). It was concluded that intrauterine proteolytic enzymes could be used to improve pregnancy rate in subclinical endometritic dairy cattle.